Lets get active: learning about Plants - Chowdhary, Eman (New Delhi The Energy and Resource Institute, 2017)
Plants are an important part of our environment. They also add beauty and colour to our surroundings. Learning about Plants explains interesting facts about plants through spot-the-difference, maze, and colouring activities, besides various simple counting and writing exercises. These easy-to-do activities promote creative thinking and problem solving among young minds, making the title a fun supplement to their textbooks. At the same time, it acquaints them with the importance of plants and trees.
Keywords: Plants; Activity book